CRISPR/Cas13 sgRNA‐Mediated RNA–RNA Interaction Mapping in Live Cells with APOBEC RNA Editing - Li‐Ting Diao; Shu‐Juan Xie; Wan‐Yi Xu; Hai‐Hui Zhang; Ya‐Rui Hou; Yan‐Xia Hu; Xin‐Xiang Liang; Jun‐Bin Liang; Qi Zhang; Zhen‐Dong Xiao (Advanced Science)
Abstract Current research on long non‐coding RNA (lncRNA) has predominantly focused on identifying their protein partners and genomic binding sites, leaving their RNA partners largely unknown. To address this gap, the study has developed a method called sarID (sgRNA scaffold assisted RNA‐RNA interaction detection), which integrates Cas13‐based RNA targeting, sgRNA engineering, and proximity RNA editing to investigate lncRNA‐RNA interactomes. By applying sarID to the lncRNA NEAT1, over one thousand previously unidentified binding transcripts are discovered. sarID is further expanded to investigate binders of XIST, MALAT1, NBR2, and DANCR, demonstrating its broad applicability in identifying lncRNA‐RNA interactions. The findings suggest that lncRNAs may regulate gene expression by interacting with mRNAs, expanding their roles beyond known functions as protein scaffolds, miRNA sponges, or guides for epigenetic modulators. sarID has the potential to be adapted for studying other specific RNAs, providing a novel immunoprecipitation‐free method for uncovering RNA partners and facilitating the exploration of the RNA‐RNA interactome.